2020
DOI: 10.1007/s00439-020-02227-2
|View full text |Cite
|
Sign up to set email alerts
|

Towards systematic nomenclature for cell-free DNA

Abstract: Cell-free DNA (cfDNA) has become widely recognized as a promising candidate biomarker for minimally invasive characterization of various genomic disorders and other clinical scenarios. However, among the obstacles that currently challenge the general progression of the research field, there remains an unmet need for unambiguous universal cfDNA nomenclature. To address this shortcoming, we classify in this report the different types of cfDNA molecules that occur in the human body based on its origin, genetic tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 88 publications
0
41
0
Order By: Relevance
“…Moreover, the authors also detected a mitochondrial mutation commonly found in patients with maternally inherited diabetes in both samples of patients with diabetes. Please see the recent review by Bronkhorst et al [13] for more details about the different nomenclature.…”
Section: Cfdna-historical Perspectivementioning
confidence: 99%
“…Moreover, the authors also detected a mitochondrial mutation commonly found in patients with maternally inherited diabetes in both samples of patients with diabetes. Please see the recent review by Bronkhorst et al [13] for more details about the different nomenclature.…”
Section: Cfdna-historical Perspectivementioning
confidence: 99%
“…Circulating DNA not associated with cells is present in the cell-free component of the whole blood, such as plasma and serum, but also in other human body fluids such as urine, saliva, and cerebrospinal fluid [1,2]. The biology of cell-free DNA (cfDNA) is not fully understood, with several possible mechanisms suggested.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, cfDNA has become an attractive subject of research as a non-invasive disease biomarker. The analysis includes many structural aspects of total cell-free DNA such as separated fractions of cf nDNA (nuclear) and cf mtDNA (mitochondrial) or cfDNA integrity [2,[6][7][8][9]. Formation of cfDNA forms does not occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is becoming increasingly recognized that the diagnostic sensitivity and specificity of mutation-based cfDNA assays can be enhanced by expanding the scope of tests to include the parallel characterization of various, potentially disease-specific, epigenetic features of cfDNA 17,18 , including (i) various classic epigenetic alterations such as histone modifications, histone variants, DNA methylation, and chromatin remodeling features [19][20][21][22] , (ii) fragment size; studies have shown that cfDNA fragment sizes differ between cancer patients (shorter fragments) and healthy controls (longer fragments) 23 , and have also been correlated with different mechanisms of release 3 , (iii) end-point fragmentation patterns and motifs [23][24][25] , and (iv) nucleosome density and spacing patterns [26][27][28] . An improved understanding of these physico-chemical features of cfDNA will not only elucidate optimal diseasedefining biomarkers, but will enable biology-informed tailoring of extraction methods for optimal capturing of target molecules or exclusion of non-target molecules, and facilitate the optimization of preanalytical steps and customization of detection technologies and bioinformatics pipelines.…”
mentioning
confidence: 99%